2006
DOI: 10.1007/s10126-006-6079-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Stock Identification of Chum Salmon in the Bering Sea and North Pacific Ocean Using Mitochondrial DNA Microarray

Abstract: A newly developed DNA microarray was applied to identify mitochondrial (mt) DNA haplotypes of more than 2200 chum salmon in the Bering Sea and North Pacific Ocean in September 2002 and also 2003, when the majority of maturing fish were migrating toward their natal river. The distribution of haplotypes occurring in Asian and North American fish in the surveyed area was similar in the 2 years. A conditional maximum likelihood method for estimation of stock compositions indicated that the Japanese stocks were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 18 publications
7
28
1
Order By: Relevance
“…Populations of chum salmon in the Bering Sea are composed of many stocks from the rivers in the Pacific Rim. The previous stock identification of individuals from mtDNA haplotypes showed that Japanese chum salmon were the dominant stock distributed in the central Bering Sea in 2002and 2004(Moriya et al, 2007Sato et al, 2007).…”
Section: Pre-migratory Chum Salmonmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations of chum salmon in the Bering Sea are composed of many stocks from the rivers in the Pacific Rim. The previous stock identification of individuals from mtDNA haplotypes showed that Japanese chum salmon were the dominant stock distributed in the central Bering Sea in 2002and 2004(Moriya et al, 2007Sato et al, 2007).…”
Section: Pre-migratory Chum Salmonmentioning
confidence: 99%
“…The hypothesis for the route of oceanic migration of chum salmon indicates that winter chum salmon of the Japanese population leave the Gulf of Alaska for the Bering Sea in spring (Urawa, 2000). In summer before the commencement of spawning migration, chum salmon originating in Japan form mixed populations with stocks from other geographical areas of the Pacific Rim in the Bering Sea, although Japanese populations are distributed mainly in the central Bering Sea (Moriya et al, 2007;Sato et al, 2007). Homing adults, which leave the Bering Sea in early summer, require two to three months to reach their natal rivers in Japan (Tanaka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Chum salmon in the Bering Sea form mixed populations whose stocks originate in the North Pacific Rim. Analyses of mitochondrial DNA (mtDNA) haplotypes showed that a considerable portion of chum salmon in these areas belongs to Japanese populations (Moriya et al, 2007;Sato et al, 2006;Sato et al, 2007).…”
Section: Oceanic and Homing Chum Salmonmentioning
confidence: 99%
“…Even though DNA markers are expected to compensate deficits of the use of allozyme analysis with increased accuracy and resolution for GSI analysis, only a few published papers have reported the utility of chum salmon mtDNA variation for GSI (Seeb and Crane 1999;Moriya et al 2007). In particular, Moriya et al (2007) applied sequence analysis for mixed-stock analysis to estimate the origin of stocks and their composition in the Bering Sea and North Pacific Ocean, and found non-random distribution of Japanese, Russian, and North American stocks in the surveyed area.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, Moriya et al (2007) applied sequence analysis for mixed-stock analysis to estimate the origin of stocks and their composition in the Bering Sea and North Pacific Ocean, and found non-random distribution of Japanese, Russian, and North American stocks in the surveyed area.…”
Section: Introductionmentioning
confidence: 99%